(untitled) (Acta Judicial Journal, 2021)
This paper will analyze the most relevant questions about the process of issuing the European arrest warrant, with reference to the procedural regulation of the European investigation order, and especially studying the intervention of the Judicial Administration Counselor and the It is desirable to increase their participation in such fundamental instruments of European criminal procedural cooperation.